2021
DOI: 10.1017/s0033291720005516
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch negativity and P3a in drug-naive adults with attention-deficit hyperactivity disorder

Abstract: Background Individuals with attention-deficit hyperactivity disorder (ADHD) often display over-response to stimuli that are irrelevant to the ongoing task, and their attentional abilities disproportionately worsen in the presence of competing stimuli. Auditory event-related potentials (ERPs) such as mismatch negativity (MMN) and P3a using the passive oddball paradigm have been studied in children and adolescents with ADHD. Still, there is no such data for adults with ADHD. This study aimed to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…More research is needed on older adult population to determine whether the CCPT is generally effective at discriminating ADHD from normative, age-related cognitive changes. Additionally, with few exceptions (Alaghband-Rad et al, 2021; Hsieh et al, 2021; Mesquita et al, 2016; Ni et al, 2016; Schweiger et al, 2007; Shang et al, 2018), most of the studies were conducted on a Caucasian, Westernized population. It is necessary for future studies to target a diverse pool of racial/ethnic participants to discover any cultural variances in CCPT performance in adults with ADHD from differing cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More research is needed on older adult population to determine whether the CCPT is generally effective at discriminating ADHD from normative, age-related cognitive changes. Additionally, with few exceptions (Alaghband-Rad et al, 2021; Hsieh et al, 2021; Mesquita et al, 2016; Ni et al, 2016; Schweiger et al, 2007; Shang et al, 2018), most of the studies were conducted on a Caucasian, Westernized population. It is necessary for future studies to target a diverse pool of racial/ethnic participants to discover any cultural variances in CCPT performance in adults with ADHD from differing cultures.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies found no significant differences in the CCPT subscales with one comparison group (e.g., Alaghband-Rad et al, 2021;Kovner et al, 1998;Solanto et al, 2004), other studies examining differences between ADHD and control participants without ADHD have found between 4 and 9 significant differences in CCPT subscales (Cohen & Shapiro, 2007;Hsieh et al, 2021;Weyandt et al, 2017). Fasmer et al (2016) used the CPT-II to distinguish between patients with ADHD versus those with other psychiatric diagnoses.…”
Section: Number Of Comparison Groupsmentioning
confidence: 99%
“…Adult ADHD patients showed significantly lower arousal levels and substantially less stable brain arousal regulation than controls ( 15 ). Compared with adult controls, it was also observed that a smaller amplitude of mismatch negativity and its differential associated pattern with inattention, real-world executive dysfunction, and poor decision-making ability in drug-naive adults with ADHD ( 16 ).…”
Section: Potential Biomarkersmentioning
confidence: 99%
“…DD has been studied widely across sensory systems including the auditory [3,7,8], visual [9,10], somatosensory [11] domains and beyond. Impairments in DD have been reported in various disorders [4], including autism [12][13][14][15][16], schizophrenia [17][18][19][20], ADHD [21][22][23] and others, highlighting the need to better understand its mechanistic underpinnings.…”
Section: Introductionmentioning
confidence: 99%